2021
DOI: 10.3390/su13126668
|View full text |Cite
|
Sign up to set email alerts
|

Critical Analysis of Methods Adopted for Evaluation of Mixing Efficiency in an Anaerobic Digester

Abstract: The effect of slurry mixing in an anaerobic digester on biogas production was intensively studied in the last few years. This subject is still debatable due to fact that this process involves three phases, solid-gas-liquid, along with the involvement of microbes during biochemical reactions, which are highly vulnerable to changes in hydrodynamic shear stresses and mixing conditions. Moreover, the complexity in the direction of optimization of mixing magnifies due to the implication of both fluid mechanics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 125 publications
0
4
0
1
Order By: Relevance
“…Regardless of how or why sludge rheology changes, the change itself may affect not only the power needed for mixing and pumping but also the AD process itself, primarily by affecting the mixing efficiency and fluid flow patterns in the reactors (interactions 5, 7, and 28 in Figure ). This aspect has long been studied in CSTBRs, mainly by performing computational fluid dynamics modeling (CFD, reviewed by refs and ). While this approach is helpful for designing reactors and dimensioning their mixing and pumping equipment, it does not necessarily provide information on when the mixing is affected to a high enough extent that effects on process performance may be expected.…”
Section: Rheology Regulation In Admentioning
confidence: 99%
“…Regardless of how or why sludge rheology changes, the change itself may affect not only the power needed for mixing and pumping but also the AD process itself, primarily by affecting the mixing efficiency and fluid flow patterns in the reactors (interactions 5, 7, and 28 in Figure ). This aspect has long been studied in CSTBRs, mainly by performing computational fluid dynamics modeling (CFD, reviewed by refs and ). While this approach is helpful for designing reactors and dimensioning their mixing and pumping equipment, it does not necessarily provide information on when the mixing is affected to a high enough extent that effects on process performance may be expected.…”
Section: Rheology Regulation In Admentioning
confidence: 99%
“…This contribution focuses on the performance of spiral ribbon mixers in non-compartmentalized stirred tanks. Singh et al [25] conducted a series of studies to analyze and optimize various forms of mixer and agitator geometries. The results obtained in the mixing process saved 7.3% of the total energy used in the process with the mixers used.…”
Section: Figure 6 Relationship Between Speed and Power Demandmentioning
confidence: 99%
“…The main purpose of the mixing operation is to provide the organisms carrying out biochemical processes with the correct working conditions by creating the appropriate degree of mixing of the bioreactor volume and maintaining it for the time specified in the technology [6,23]. The mixing phase is usually implemented using mechanical stirrers so that the sludge at the bottom of the chamber comes into contact with the raw wastewater introduced into the system during the filling phase [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed how the results of the optimization of mixing in digesters can vary. In addition, the data regarding the rheology of the slurry, the impeller, and the digester design are missing in most studies, which is a very important aspect to evaluate the mixing in any vessel because the mixing operation is a physical process [29]. The present study investigated the effect of increasing the mixing interval time on the efficiency of the AD process and overall BY.…”
Section: Introductionmentioning
confidence: 99%